A survey of East Palaearctic Gnaphosidae (Araneae). 5. On Synaphosus from Central Asia - Marusik, Yuri M.; Fomichev, Alexander A. (Zootaxa, 2016)
Four new species of Synaphosus are described from Central Asia: S. shmakovi sp. n. (♀, Western Mongolia), S. ovtsharenkoi sp. n. (♂♀, Central Mongolia), S. mongolicus sp. n. (♀, South-Western Mongolia) and S. saidovi sp. n. (♀, Tajikistan). New faunistic records and illustrations of S. palearcticus Ovtsharenko, Levy & Platnick, 1994 and S. turanicus Ovtsharenko, Levy & Platnick, 1994 are provided. Synaphosus with three named species is recorded for the first time from Mongolia, and S. palearcticus is reported for the first time from Tajikistan.